Pharmacy Student’s Knowledge of Diabetes and Obesity: ACross-Sectional Study in Dharashiv, India - Akoskar, Sneha; Jha, Deepak; Hangargekar, Pallavi; Kulkarni, Dipti; Joshi, Amol; Jain, Ashish (Indian Journal of Pharmacy Practice)
Introduction: The prevalence of diabetes and obesity is rising globally, necessitating effective management strategies. Adequate understanding of these conditions among healthcare professionals, including pharmacy students, is crucial for effective prevention and management. This study explores the association between course (B.Pharm/Pharm.D) curriculum and student’s knowledge about diabetes and obesity, emphasizing the understanding of pathogenesis, risk factors and management. Materials and Methods: A cross-sectional observational study at ASPM’s K. T. Patil College of Pharmacy included 346 participants. Ethical considerations were addressed and a self-administered questionnaire assessed pharmacy student’s knowledge of diabetes and obesity. Twenty-two closed-ended questions with response options of “true,” “false,” and “don’t know” were used. Results: A total of 346 students’ participated, with significant differences in correct responses between B.Pharm and Pharm.D students for diabetes and obesity-related questions. These findings highlight the impact of educational level on understanding these conditions. Conclusion: Our investigation highlights patterns and disparities in knowledge gaps among pharmacy students regarding diabetes and obesity. Integrating targeted modules and practical training into pharmacy curricula can enhance understanding and management of these conditions, ultimately improving healthcare outcomes.
Keywords: Diabetes; Obesity; Pharmacy education; Knowledge disparities; Cardiovascular health